Au-nanocrystals-decorated δ-MnO2 as an efficient catalytic cathode for high-performance Li–O2 batteries1. Issue 21 (7th June 2015) - Liu, Shuangyu; Wang, Guoqing; Tu, Fangfang; Xie, Jian; Yang, Hui Ying; Zhang, Shichao; Zhu, Tiejun; Cao, Gaoshao; Zhao, Xinbing
<x xml:space="preserve">Abstract</x> Porous Au/δ-MnO2 on graphene-coated Ni foam exhibited a superior catalytic effect for Li–O2 batteries with Au-induced directed Li2O2 growth.